Legal definition of remote work in Polish labour law - Pietrzak, Ewa (Z Problematyki Prawa Pracy i Polityki Socjalnej, 2025)
Legal regulation of remote work was introduced to the Polish Labour Code by the Act of 1 December 2022 amending the Labour Code and certain other acts, which entered into force on 7 April 2023. The new legislation includes a legal definition of remote work. Remote work is a broader concept than the previously existing definitions of telework and teleworker. The essence of remote work is that it is carried out at a place indicated by the employee and agreed in each case with the employer, this place being outside the employer’s premises.